2009
DOI: 10.1111/j.1467-789x.2009.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary strategy to manipulate ad libitum macronutrient intake, and glycaemic index, across eight European countries in the Diogenes Study

Abstract: SummaryThe aim of this study was to describe the development and implementation of a multifaceted, low-fat, weight-loss strategy for a Pan-European randomized controlled dietary intervention study, Diogenes. There were 891 families with at least one overweight/obese parent who underwent screening. Eligible, overweight/ obese adults followed an 8-week weight-loss phase with a fixed low-energy diet (800 kcal). On attaining weight loss of Ն8%, families were randomized to a 6-or 12-month low-fat (25-30%E) diet eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
115
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 20 publications
(19 reference statements)
0
115
0
Order By: Relevance
“…A detailed description of the Diogenes intervention trial can be found elsewhere (Larsen et al, 2010a;Moore et al, 2010;Saris & Harper, 2005).…”
Section: Study Samplementioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the Diogenes intervention trial can be found elsewhere (Larsen et al, 2010a;Moore et al, 2010;Saris & Harper, 2005).…”
Section: Study Samplementioning
confidence: 99%
“…Specific details on the diets and the dietary counselling are given in a separate publication (Moore et al, 2010).…”
Section: Study Samplementioning
confidence: 99%
“…Details of the methodology of the project are given in papers by Larsen et al (2009) and Moore et al (2009).…”
Section: Experimental Designmentioning
confidence: 99%
“…The main aspects of the research conducted in the comprehensive, long-term, randomised, controlled dietary intervention study were to address the impact of dietary protein and glycaemic index (GI) on weight (re)gain in a large number of families in which parents and children suffer from obesity or overweight. A detailed description of the study and further information on the study recruitment, exclusion criteria and the investigations carried out at the clinical investigation days have been described in two methodological papers (Larsen et al 2010b;Moore et al 2010). The study population in the present study consisted of the adult members of the families participating in the intervention study carried out in the Danish centre.…”
Section: Methodsmentioning
confidence: 99%
“…The latter implies that both the LGI and the HGI diets had quite a substantial range in GL. A detailed description of the diets and the dietary strategy is described elsewhere (Aston et al 2010b;Moore et al 2010). Alcohol consumption was allowed in accordance with the current guidelines issued by the Danish National Board of Health, i.e., \14 units/week and \21 units/week (1 unit = 12 g alcohol) for women and men, respectively.…”
Section: Experimental Dietsmentioning
confidence: 99%